Energy usage and drying capacity of flat-bed and inclined-bed dryers for rough rice drying - Ghiasi, M.; Ibrahim, Mohd Nordin; Kadir Basha, Roseliza; A. Talib, Rosnita (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The evaluation of a dryer performance in terms of energy consumption, drying capacity and quality of final product is the main concern of rice milling industry at any time. A study was implemented to investigate on the benefits of common drying practices by studying the drying performances of flat-bed and inclined-bed dryers which are popular in rice industry in Malaysia and neighbouring countries. For this purpose, flat-bed dryer (FBD) and inclined-bed dryer (IBD) were designed, fabricated and operated in the laboratory based on actual industrial drying conditions. The results revealed that inclined-bed drying significantly increased drying capacity (ton m-2 h-1) of up to 25 % at drying temperature of 42-43°C and almost 29 % at 38-39°C drying air temperature compared to flat-bed drying. Furthermore, overall drying energy consumption in IBD was found to vary between 78.6 to 91.97 kW.h ton-1, while for FBD the energy consumption was more than 200 kW.h ton-1 for both levels of drying air temperatures. Both dryers were found to produce rice with desired/ acceptable commercial quality index, even though the head rice yields of FBD were higher than that of IBDs.